2023
DOI: 10.28991/cej-sp2023-09-05
|View full text |Cite
|
Sign up to set email alerts
|

Concept of an Intelligent Parking System; Efforts to Resolve Traffic Conflicts Regulations

Abstract: Makassar, an Indonesian city, is situated on the south-western coast of Sulawesi Island. It is the largest commercial centre in eastern Indonesia, and traffic congestion is a problem there. Movement management must establish sufficient and well-organized parking areas, as well as a good and transparent system to eliminate unmonitored restitution funds, in order to address these issues. To address parking issues in Makassar, a legal and technical strategy is developed, with an emphasis on inclusiveness and incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Field observations showed that a high number of the motorists in Basra City are illegally parking on streets and sometimes they are even doing double parking on curb. This needs further investigations, since the on streets parking has a significant impact on reducing road capacity [28]. Yousif and Purnawan [29] reported that on busy roads inappropriate parking can lead to sever delays.…”
Section: Results Discussionmentioning
confidence: 99%
“…Field observations showed that a high number of the motorists in Basra City are illegally parking on streets and sometimes they are even doing double parking on curb. This needs further investigations, since the on streets parking has a significant impact on reducing road capacity [28]. Yousif and Purnawan [29] reported that on busy roads inappropriate parking can lead to sever delays.…”
Section: Results Discussionmentioning
confidence: 99%
“…N p Minimize C t [30] Time to full capacity utilization This parameter measures the time for filling all the slot assignments. Ft = t − t Full_assign Maximize Ft [26] Priority assignment This parameter measures the average of assigned slots with the specified priority.…”
Section: Parameter Description Calculation Objective Referencementioning
confidence: 99%
“…Kaplan & Clapper [20] reported that most of the traffic congestion problems on university campuses occurred around campus gates or near parking facilities. Additionally, several previous studies reported that on-street parking [21] and inappropriate parking manoeuvres [22] can cause traffic congestion and higher delays.…”
Section: Previous Studiesmentioning
confidence: 99%